Australian Legendary Tales: folk-lore of the Noongahburrahs as told to the Piccaninnies - Parker, K. Langloh (Katie Langloh), 1856-1940 (Salt Lake City, UT : Project Gutenberg, 2003)
"Australian Legendary Tales: folk-lore of the Noongahburrahs as told to the..." by K. Langloh Parker is a collection of Aboriginal Australian stories published in 1896. Told to Parker by the Noongahburrah people, these tales unfold in a timeless world where animal spirits, supernatural beings, and humans interact. The stories feature the All Father Baiame, the culture hero Wurrunnah, and various animal beings, often touching on themes of creation. This groundbreaking work marked the first substantial representation of Aboriginal Australian cultural traditions in English literature. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Australian_Legendary_Tales
Release date is 2003-03-01
Produced by Col Choat. HTML version by Al Haines.
Keywords: Folklore -- Australia